DAMPAK PENETRASI BANK ASING TERHADAP KINERJA KEUANGAN BANK ISLAM DI INDONESIA - Wiwiek Rabiatul Adawiyah (Jurnal Keuangan dan Perbankan, 2015)
This article empirically examined the effects of foreign banks entry on the performance of Islamic banks inIndonesia, with the observation period 1999-2013. The method of analysis employed was descriptive statisticsand multiple regressions. The result of the study indicated that capital adequacy ratio had a negative influenceon the financial performance, measured using return on assets (ROA) of domestic Islamic banks in Indonesiawhile liquidity ratio did not influence ROA. Surprisingly this study revealed that foreign banks entry had anegative effect, insignificant influence on the financial performance of Islamic banks. This result supported theviews that foreign banks entry had an adverse effect on the performance of domestic banks in several emergingmarket economies worldwide, but against the notion that foreign banks entry brought positive effects on theperformance of incumbent banks.